(untitled) (Indian Journal of Public Health Research & Development, 2020)
Thailand has imposed strong tobacco control policies to reducing smoking. The effectiveness of those measures towards reducing smoking especially among youths still unknown. This study aimed to determine the effectiveness of law enforcement on tobacco control among youth in the Northeast of Thailand. This cross-sectional study was conducted among 1,147 youths who were recruited by using a multistage random sampling from 6 universities in the Northeast of Thailand. A self-administered structured questionnaire was used to collect the data. The Generalized Linear Mixed Model was used to determine the association between law enforcement on tobacco control and smoking when controlling for other covariates. The results show that 20.1% were current smokers. Law enforcement on tobacco control and smoking that were significantly associated with smoking among youths were had low level of awareness on tobacco raising price, antismoking campaign, smoke-free in public areas, not showing pack, price and brand of cigarette at point of sale product, pictorial health warnings and not distributing cigarette with tax avoidance/tax evasion. The other covariates were male gender, alcohol drinker, had low level of attitude on not smoking, had smokers close friend and had smoker father. One-fourth of youths in the Northeast of Thailand were current smokers. Legal measures had influence on youths’ smoking as well as gender, family and friends.